2014
DOI: 10.1177/0885066613517076
|View full text |Cite
|
Sign up to set email alerts
|

Hemophagocytic Syndrome and Critical Illness

Abstract: Hemophagocytic lymphohistiocytosis (HLH) comprises a heterogeneous group of diseases which are characterized by a hyperinflammatory state due to uncontrolled T cell, macrophage and histiocyte activation, accompanied by excessive cytokine production. This rare condition is almost uniformly fatal unless promptly recognized and treated. Much progress has been made in the last two decades in our understanding of the mechanisms underlying familial, and to a lesser extent, acquired cases of HLH. Recurrent mutations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 83 publications
1
61
1
Order By: Relevance
“…One hypothesized mechanism is that the infectious viral protein of the trigger inappropriately activates cytotoxic and helper T cells, which leads to excessive and uncontrolled cytokine release resulting in tissue damage [4, 7]. An additional hypothesis is that defective T cells and NK cells fail to properly remove antigen resulting in ongoing uncontrolled macrophagic activity [4, 7]. Soluble interleukin-2 receptor (soluble CD25) reflects the activation of T cells and NK cell activity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…One hypothesized mechanism is that the infectious viral protein of the trigger inappropriately activates cytotoxic and helper T cells, which leads to excessive and uncontrolled cytokine release resulting in tissue damage [4, 7]. An additional hypothesis is that defective T cells and NK cells fail to properly remove antigen resulting in ongoing uncontrolled macrophagic activity [4, 7]. Soluble interleukin-2 receptor (soluble CD25) reflects the activation of T cells and NK cell activity.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that ferritin levels > 10,000 ug/L had 90% sensitivity and 96% specificity for HLH in a 2008 pediatric study [9]. It has been also shown that higher ferritin level at the time of diagnosis is associated with poorer prognosis and higher mortality [1-4]. It is therefore used as a prognostic factor to monitor the treatment effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In patients diagnosed with HLH, ferritin levels reflect disease course and activity, and in children a marked decrease in ferritin (>96%) portends decreased short term mortality during HLH treatment [25]. In critically ill adults, however, the increased prevalence of conditions which elevate ferritin, such as infection, malignancy, autoimmune disease, liver injury and chronic blood transfusion make hyperferritinemia a nonspecific finding for HLH [26,27]. Only 3% of hospitalized patients with elevated ferritin levels (>2000 ng/mL) will have a diagnosis of HLH; patients are more likely to have liver injury or infection with elevated ferritin alone [28].…”
Section: Diagnosis and Biomarker Testingmentioning
confidence: 99%